N‐acetylgalactosaminyltransferase‐4 protects against hepatic ischemia/reperfusion injury by blocking apoptosis signal‐regulating kinase 1 N‐terminal dimerization - Zhou, Jiangqiao; Guo, Lina; Ma, Tengfei; Qiu, Tao; Wang, Sichen; Tian, Song; Zhang, Li; Hu, Fengjiao; Li, Wei; Liu, Zhen; Hu, Yufeng; Wang, Tianyu; et al. (Hepatology (Baltimore, Md.), 2022)
Background and Aims Ischemia‐reperfusion (I/R) injury is an inevitable complication of liver transplantation (LT) and compromises its prognosis. Glycosyltransferases have been recognized as promising targets for disease therapy, but their roles remain open for study in hepatic I/R (HIR) injury. Here, we aim to demonstrate the exact function and molecular mechanism of a glycosyltransferase, N‐acetylgalactosaminyltransferase‐4 (GALNT4), in HIR injury. Approach and Results By an RNA‐sequencing data‐based correlation analysis, we found a close correlation between GALNT4 expression and HIR‐related molecular events in a murine model. mRNA and protein expression of GALNT4 were markedly up‐regulated upon reperfusion surgery in both clinical samples from subjects who underwent LT and in a mouse model. We found that GALNT4 deficiency significantly exacerbated I/R‐induced liver damage, inflammation, and cell death, whereas GALNT4 overexpression led to the opposite phenotypes. Our in‐depth mechanistic exploration clarified that GALNT4 directly binds to apoptosis signal‐regulating kinase 1 (ASK1) to inhibit its N‐terminal dimerization and subsequent phosphorylation, leading to a robust inactivation of downstream c‐Jun N‐terminal kinase (JNK)/p38 and NF‐κB signaling. Intriguingly, the inhibitory capacity of GALNT4 on ASK1 activation is independent of its glycosyltransferase activity. Conclusions GALNT4 represents a promising therapeutic target for liver I/R injury and improves liver surgery prognosis by inactivating the ASK1‐JNK/p38 signaling pathway.